Retaining wall / Nur Fatin Azini Mohd Zulkifli - Mohd Zulkifli, Nur Fatin Azini (Universiti Teknologi MARA, Perak, 2019)
Main objective of this report is to develop the knowledge about the reinforcement concrete retaining wall based on findings through the analysis of designing the stabilization of retaining wall. A qualitative case study technique has been used in this paper for the data collection and analysis. First and foremost, data and information gather from references book, past research, articles and internet sources.